Kidney loss due to periureteral fibrosis and ureteral obstruction secondary to migration of subureterically injected calcium hydroxylapatite - (:unkn) unknown (My University, 2006)
Vesicoureteral reflux (VUR) is one of the significant urologic diseases of childhood and its endoscopic treatment is a viable option in terms of both simplicity and reduced morbidity. However, despite intensive research, no ideal injection material that yields the best long-term results with the least side effects has been introduced as yet. Synthetic calcium hydroxylapatite is one of the materials that has recently been under trial. Although favorable short-term success rates have been reported with the subureteric injection of calcium hydroxylapatite without any side effects, this case report shows its potential to migrate. To our knowledge, we present the first case where the migration of subureterically injected calcium hydroxylapatite resulted in periureteral fibrosis, ureteric obstruction and subsequent renal loss. © 2005 Journal of Pediatric Urology Company.
Keywords: Injection; Migration; Treatment; Vesicoureteral reflux